Rare cavernous haemangioma arising in the temporalis muscle: a clinical case and review - Suresh, Priyanka; Ramesh Babu, Akshay Singh; Chandrabhan Singh , Ramesh Babu (International Surgery Journal, 2025)
Haemangiomas are benign vascular neoplasms characterized by an abnormal proliferation of blood vessels and can occur in any vascularized tissue, including the skin, subcutaneous tissue, muscle, and bone. Intramuscular haemangioma, a distinctive type of haemangioma within the skeletal muscle, account for <1% of all haemangiomas and temporalis muscle is a very uncommon site. This report describes a case for a 71-year-old man, who underwent an excision of lump from left scalp, at day surgery unit in King's college hospital London. The patient had noticed two lumps, one on his right neck and one on the left sides of his scalp which had been increasing in size and causing him discomfort. Surgical excision was performed under local anaesthesia with a differential diagnosis of a lipoma. The lump presented under the muscular plane was found to be very vascular with no typical features of a lipoma and this appeared to be haemangioma or haemangiolipoma, histopathology later confirmed-a cavernous haemangioma with focal thrombosis and recanalization. This case report includes imaging findings, intraoperative findings and histology findings which are discussed with a review of the current literature on this subject